ABO and RhD blood group antigen frequencies in patients and blood donors: Implications for the U.S. blood supply - Elizabeth S. Allen; Sara Bakhtary; Sarah E. Barnhard; Roksolana Demianets; Gagan Mathur; Catherine Mazzei; Zhen Mei; Suzanne L. Wheeler; Khalda A. Ibrahim (PLOS One, 2026)
Background ABO/Rh blood groups play a pivotal role in the practice of transfusion medicine. To our knowledge, there have been no large studies reporting these blood group antigen frequencies in the United States (US) since 2004, and the most recent large study only reported antigen frequencies for donors, not patients. We sought to determine and compare the ABO/RhD antigen frequencies in patient and donor populations. Methods In this multi-center retrospective cohort study, five California academic medical centers and one national blood center reviewed blood group and demographic data from patients, California blood donors, and US blood donors who underwent ABO/RhD typing during a 5-year period. Data were analyzed to characterize each population and to compare the patient and donor populations. Results ABO/RhD typing for 467,748 patients, 719,211 California blood donors, and 7,449,831 US blood donors were included in this study. Among patients, California donors, and US donors, group O was represented by 46.2%, 50.8%, and 48.8% of the population, respectively; group A 35.8%, 32.1%, and 36.0%; group B 14.1%, 13.0%, and 11.3%; and group AB 3.9%, 4.1%, and 3.9%. Among patients, California donors, and US donors, RhD-positive individuals represented 90.0%, 88.4%, and 83.0% of the population. Patient ABO/RhD frequencies varied significantly by site, age, and sex, and differed from the ABO/RhD frequencies of California and US donors. Conclusions This study reports ABO/RhD frequencies in a large cohort of California patients, California blood donors, and US blood donors, which may inform donor recruitment, inventory management, and policy development. Patient and donor ABO/RhD frequencies differ significantly, indicating potential misalignment that may be consequential and warrants investigation.